Noise and Bandwidth Consideration in Designing Op-Amp Based Transimpedance Amplifier for VLC - Trio Adiono; Rachmad Vidya Wicaksana Putra; Syifaul Fuada (Institute of Advanced Engineering and Science, 2018)
In a visible light communication (VLC) system, there are many modules involved. One of the important modules is Transimpedance Amplifier (TIA) that resides in the analog front-end receiver (Rx-AFE). TIA is responsible for performing signal conversion from current signal, which is provided from the photodiode (PD) to voltage signal. It is the reason why the TIA should be operating in low noise condition and wide bandwidth of frequency. These will enable a flexible coverage of the VLC system in performing its signal processing. Hence, in this research, we provide considerations of the noise and frequency bandwidth analysis in designing TIA to cope with the required design specification of a VLC system.